An innovative resilient rocking column with replaceable steel slit dampers: Experimental program on seismic performance. (15th March 2019) - Liu, Yang; Guo, Zixiong; Liu, Xiaojuan; Chicchi, Rachel; Shahrooz, Bahram
Highlights: Proposing an innovative resilient rocking column. Quasi-static cyclic loading on a series of IRR columns. Achieving resilience of IRR columns using replaceable steel slit dampers. Simplified model to predict the load-carrying capacity. Abstract: Six large-scale experimental tests were conducted to investigate the behavior of an innovative resilient rocking (IRR) column subjected to quasi-static cyclic loading. The IRR column subassembly consists of a steel column that rocks and is connected at its base with replaceable steel slit dampers. This system is capable of achieving rapid restoration of structural functionality after earthquakes, which has recently emerged as an important issue facing the structural engineering profession. This paper describes the load-carrying mechanism of the system, presents experimental test results, and proposes a simplified method for calculating the horizontal load-carrying capacity. The primary experimental test variables are the thickness of steel slit dampers, axial compression ratio, and shear span-depth ratio of the column. Test results showed that IRR columns performed satisfactorily in terms of strength and stiffness, ductility, and stable hysteretic behavior. Two of the IRR columns were repaired in situ after being subjected to 3% drift and were subsequently loaded up to 5% drift. The performance of the repaired specimens was nearly the same as their counterparts before repair, indicating that replacement is feasible. The maximum horizontal load-carrying capacity of the IRR column, which was calculated using the proposed design method, produced reasonably conservative estimates of the experimentally measured values.